PEMANFAATAN MEDIA MAZE DALAM PROSES PEMBELAJARAN DI PAUD AR-RAUDHAH KACE TIMUR - Sari, Rizki Novita (ICEJ : Islamic Childhood Education Journal, 2022)
The use of maze media in learning is considered interesting for children and able to develop several aspects of child development. This is the reason the researchers conducted research at PAUD Ar-Raudhah Kace Timur, because it is rare to find schools that use labyrinths as a medium for early childhood learning. This research is a qualitative research, which provides a report on research results by describing and explaining the data obtained regarding the use of labyrinth media in the learning process at PAUD Ar-Raudhah Kace Timur. Sources of data obtained are primary data sources obtained from interviews and observations and secondary data obtained from books, articles and theses. The data collection methods in this study used structured interviews, non-participant observation and documentation. While the data analysis method uses data reduction, displays data and conclusions based on the facts that have been found from the research results.Results Based on the research, it shows that the maze media used in learning at PAUD Ar-Raudhah Kace Timur can improve some children's development, first, the maze media can improve children's motor development which is judged by the fact that the child is able to hold the maze media correctly and move the media when play. Second, increasing aspects of emotional social development, namely children are able to train their patience to wait their turn, are able to work together and children can express both when they lose and when they win. Third, it can improve children's cognitive development, which is marked by the child's ability to recognize object names, shapes, sizes and colors from maze media.